1987
DOI: 10.1113/jphysiol.1987.sp016461
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting intracellular sodium during repetitive activity in isolated sheep Purkinje fibres.

Abstract: SUMMARY1. Intracellular Na+ activity (a'a) was measured using neutral-carrier Na+-sensitive micro-electrodes in voltage-clamped sheep Purkinje fibres during and after 4 min sequences of depolarizing pulses applied to around 0 mV, at a rate of 2-5 Hz. After trains of pulse duration 50 ms the mean increase in aka was 0-65 + 0-3 mM (mean+ S.D., n = 18) whereas with longer pulse durations this rise became progressively smaller. At pulse durations of 300 ms a fall in aka was usually found.2. Recovery of aka after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

1987
1987
1995
1995

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 51 publications
(83 reference statements)
1
25
0
1
Order By: Relevance
“…We have previously shown that the change of aka during a train of voltage-clamp pulses is variable and aka can rise or fall according to the experimental conditions and the preparation (Boyett et al 1987). One of our earliest observations was that if aka rose during the train there was invariably a slow rise in force (which we describe as a ' positive staircase') whereas if aia fell there was frequently a progressive decline of force throughout much of the train (a 'negative staircase').…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that the change of aka during a train of voltage-clamp pulses is variable and aka can rise or fall according to the experimental conditions and the preparation (Boyett et al 1987). One of our earliest observations was that if aka rose during the train there was invariably a slow rise in force (which we describe as a ' positive staircase') whereas if aia fell there was frequently a progressive decline of force throughout much of the train (a 'negative staircase').…”
Section: Resultsmentioning
confidence: 99%
“…aNa AND THE FORCE STAIRCASE Na+-sensitive micro-electrodes. For reasons discussed elsewhere (Boyett et al 1987), at the start and end of a voltage-clamp train there was a transient deflection of the aia signal, and during the train the ala signal could be shifted up or down. Both of these features are artifacts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…33 If the hormonal environment leads to increased cAMP levels, the activation range of the pacemaker current would be shifted in a positive direction,34 contributing to a Na+ influx even for depolarized Vm.…”
Section: Discussionmentioning
confidence: 99%